Unexpected higher resilience to distraction during visual working memory in schizophrenia - Ru-Yuan Zhang; Yi-Jie Zhao; Li Zhang; Xuemei Ran; Ji Chen; Yixuan Ku (Schizophrenia)
Abstract This study investigates the computational mechanisms underlying visual working memory (VWM) deficits in schizophrenia (SZ) under distraction. Combining 60 SZ patients and 61 demographically matched healthy controls (HC), we employed a modified delayed-estimation task with varying set sizes (1/3) and distractor numbers (0/2). Results showed universally impaired VWM performance in SZ across conditions, though distraction did not disproportionately worsen their deficits. Using the variable precision model, we found that distractors significantly increased resource allocation variability (reflecting heterogeneity in attentional resource distribution) in HC, but not in SZ. This counterintuitive pattern suggests SZ patients’ VWM processes are less perturbed by external distractions, potentially linked to reduced flexibility in cognitive control. Our findings highlight the nonlinear interplay of multiple cognitive dysfunctions in SZ, where their combined effects exceed simple additive models, offering new insights into the mechanistic complexity of cognitive deficits in the disorder.